2022
DOI: 10.3390/polym14050950
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Drug Conjugates: A Tool for Enhanced Cancer Therapy

Abstract: Cancer is one of the most widespread deadly diseases, following cardiovascular disease, worldwide. Chemotherapy is widely used in combination with surgery, hormone and radiation therapy to treat various cancers. However, chemotherapeutic drugs can cause severe side effects due to non-specific targeting, poor bioavailability, low therapeutic indices, and high dose requirements. Several drug carriers successfully overcome these issues and deliver drugs to the desired sites, reducing the side effects. Among vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 159 publications
0
20
0
Order By: Relevance
“…In addition, it is well-known that natural polymers such as polysaccharides possess inherent biocompatibility and biodegradability, and thus have been widely used for drug delivery system, including anti-cancer drugs (49,50). It was reported that even subtle differences in polymer Mw (such as a few kilodaltons) can affect the efficiency of the drug delivery system using polysaccharides (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well-known that natural polymers such as polysaccharides possess inherent biocompatibility and biodegradability, and thus have been widely used for drug delivery system, including anti-cancer drugs (49,50). It was reported that even subtle differences in polymer Mw (such as a few kilodaltons) can affect the efficiency of the drug delivery system using polysaccharides (51).…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of alginate drug delivery vehicles have been prepared, such as microspheres, tablets and nanoparticles. [214] Kianersi at al. [227] prepared alginate nanoparticles for the delivery of betamethasone sodium phosphate, an anti-inflammatory drug via electrospraying, emulsification and a combination of these two methods.…”
Section: Polysaccharides Used In Drug Delivery Systemsmentioning
confidence: 99%
“…HA-based drug delivery vehicles are generally in the forms of hydrogel or micelles. [214] Yan et al [224] successfully prepared micelles based on hyaluronic acid-tetraphenyl ethylene conjugate (HA-SS-TPE) with glutathione (GSH) for targeted drug delivery of doxorubicin (DOX). Doxorubicin was incorporated during the self-assembly of HA-SS-TPE, to form DOX-loaded micelles.…”
Section: Polysaccharides Used In Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracted pectin is mainly used in the food industry as gelling, thickening, emulsifying, and stabilizing agents in a variety of foods [5]. Recently, pectin was also used in the production of edible film coatings [6] as well as drug nanocarriers [7,8]. The recognized biological activities of pectin are very diverse, including the ability to lower serum lipids, cholesterol, and glucose levels, as well as prebiotic activity (reviewed in [9]).…”
Section: Introductionmentioning
confidence: 99%